Unraveling the Interplay of Learning Agility, Burnout, and Executive Function in Fostering Agile Leadership among Millennial Leaders - Widhianingtanti, Lucia Trisni; Suhariadi, Fendy; Handoyo, Seger; Luijtelaar, Gilles van (RSF Conference Series: Business, Management and Social Sciences, 2023)
In the rapidly evolving business landscape, agile leadership, especially among millennial leaders, has become pivotal. However, a comprehensive understanding of how Learning Agility, Burnout, and Executive Function interact to shape this leadership style is still limited, with burnout potentially impeding agile leadership development. This study aimed to elucidate the interplay between Learning Agility, Burnout, Executive Function, and their collective contribution to Agile Leadership among millennial leaders. We selected 121 millennial leaders from five different companies for this purposeful study. Utilizing Model 8 in Process Macro Hayes, we tested four hypotheses to evaluate the relationships between Learning Agility (LA) and Agile Leadership (AL), the mediating role of Executive Function (EF), the moderating effect of Burnout, and the conditional indirect impact of EF at various burnout levels. The results revealed a significant positive correlation between Learning Agility and Agile Leadership when Burnout was extremely low (p < 0.01). Still, this relationship was not significant at neutral and high burnout levels. While executive function emerged as a crucial mediator, it did not significantly mediate the Learning Agility-Agile Leadership relationship. Burnout was found to moderate this relationship, accounting for an additional 4.96% of the variability in Agile Leadership (p < 0.01), I would write p<.01). The overall model explained 17.18 (17.2) % of Agile Leadership variability (F = (6.0150 =) 6.02, (p = 0.0002), p<.001). However, the conditional indirect effects of Learning Agility on Agile Leadership were not statistically significant at different burnout levels. It can be concluded that Burnout is a significant moderator variable between Learning Agility and Agile Leadership among millennial leaders, emphasizing the need for Burnout reduction strategies to optimize the influence of Learning Agility on Agile Leadership. Future research is required to fully understand the mediating role of Executive Function in this relationship.